When feeling positive is being “in the zone”: How challenge optimality causes changes in positive affect and flow - Man-Chung Fung; Christopher Jackson (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2024)
Flow is a state of highly focused attention, associated with player loyalty (thus sought after among game designers). We investigate the link between positive affect (hereby PA) and flow experience. According to the literature, games should ideally induce PA in players and that this might induce higher flow in games at optimal challenge (challenge that matches the player’s skills). We, however, propose that PA and the flow state form a negative feedback loop, where PA could reduce future flow, depending on the challenge conditions. We conducted two experiments, with 144 and 338 university students as participants, respectively. The experiments showed that under the optimal challenge condition, current PA is negatively linked to future flow. Based on this, we propose that game designers should be cautious about the use of PA-inducing stimuli, as they might form a negative feedback loop with flow.